2015
DOI: 10.3109/15412555.2015.1043517
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Hospital Care for Exacerbation of COPD: Is Inhaled Maintenance Therapy Modified?

Abstract: Combinations of drugs with distinct and complementary mechanisms of action may offer improved efficacy in the treatment of chronic obstructive pulmonary disease (COPD). In two 12-week, double-blind, parallel-group studies, patients with COPD were randomized 1:1:1 to once-daily umeclidinium (UMEC; 62.5 μg and 125 μg) 
or placebo (PBO), added to twice-daily fluticasone propionate/salmeterol (FP/SAL; 250/50 μg). In both studies, the primary efficacy measure was trough forced expiratory volume in 1 second (FEV1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Data from an United States administrative data set analysis suggest that AECOPD account for approximately 0.8% of ED visits, that 49% of patients were hospitalized after an ED visit for COPD and that average length of stay (LOS) was approximately 4 days . European studies report admission rates of up to 65% . There is minimal detailed data about demographic and clinical features, assessment, treatment and outcome of patients with AECOPD treated in ED of Australasia and South East Asia (SEA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from an United States administrative data set analysis suggest that AECOPD account for approximately 0.8% of ED visits, that 49% of patients were hospitalized after an ED visit for COPD and that average length of stay (LOS) was approximately 4 days . European studies report admission rates of up to 65% . There is minimal detailed data about demographic and clinical features, assessment, treatment and outcome of patients with AECOPD treated in ED of Australasia and South East Asia (SEA).…”
Section: Introductionmentioning
confidence: 99%
“…1 European studies report admission rates of up to 65%. 2 There is minimal detailed data about demographic and clinical features, assessment, treatment and outcome of patients with AECOPD treated in ED of Australasia and South East Asia (SEA).…”
Section: Introductionmentioning
confidence: 99%
“…Use of ICS-based treatment regimens should be carefully considered because their long-term use is associated with the risk of side effects, such as pneumonia, osteoporosis, and diabetes, and increased economic burden (132). An observational study involving patients with COPD exacerbations presenting to the ED showed that emergency care did not usually include changes in inhaled maintenance treatment (133). GOLD recommends that maintenance treatment should be tailored to a patient's needs based on individualized assessment of symptoms and future risk of exacerbations (1).…”
Section: Indications For Discharge From the Edmentioning
confidence: 99%